2016
DOI: 10.1093/mnras/stw1697
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of elliptical galaxies with planetary nebulae in modified Newtonian dynamics

Abstract: The dynamics of an elliptical galaxy within a couple of effective radii can be probed effectively by stars. However, at larger distances planetary nebulae (PNe) replace stars as the tracer of the dynamics. Making use of the motion of PNe, Romanowsky et al. (2003) measured the dynamics of three luminous elliptical galaxies (NGC821, NGC3379 and NGC4494) at large distances from the galactic center. They found that little dark matter is needed up to 6 effective radii. Milgrom & Sanders (2003) showed that this res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…For low surface mass density ones (Σ < Σ0), the mass discrepancy is large (for review, see, e.g., Sanders & McGaugh (2002); Famaey & McGaugh (2012)). In fact, the same trend happens in elliptical galaxies, for instances, high surface mass density elliptical galaxies probed by planetary nebulae have small mass discrepancy (Romanowsky 2003;Milgrom 2003;Tian & Ko 2016), and for low surface mass density tidal dwarfs the mass discrepancy is large (Gentile et al 2007;Milgrom 2007;Dabringhausen et al 2016). Recently, from the surface mass density in the central regions of 135 disk galaxies (S0 to dIrr), Lelli et al (2016) showed that the mass discrepancy increases as surface mass density decreases.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…For low surface mass density ones (Σ < Σ0), the mass discrepancy is large (for review, see, e.g., Sanders & McGaugh (2002); Famaey & McGaugh (2012)). In fact, the same trend happens in elliptical galaxies, for instances, high surface mass density elliptical galaxies probed by planetary nebulae have small mass discrepancy (Romanowsky 2003;Milgrom 2003;Tian & Ko 2016), and for low surface mass density tidal dwarfs the mass discrepancy is large (Gentile et al 2007;Milgrom 2007;Dabringhausen et al 2016). Recently, from the surface mass density in the central regions of 135 disk galaxies (S0 to dIrr), Lelli et al (2016) showed that the mass discrepancy increases as surface mass density decreases.…”
Section: Introductionmentioning
confidence: 73%
“…The discrepancy is larger when the gravitational acceleration of the spiral galaxy is smaller, and the relation is called the mass discrepancy-acceleration relation (MDAR). Later, the MDAR is also confirmed by the dynamics of elliptical galaxies (Tian & Ko 2016;Janz et al 2016). However, mass discrepancy shows no clear relation to other observational quantities such as distance or orbital angular speed (see McGaugh (2004) for details).…”
Section: Introductionmentioning
confidence: 96%
“…Since the seminal papers by Milgrom (1983a,b,c), MOND has been applied to several astrophysical objects including (in order of increasing size) wide binary stars (Hernandez, Jiménez & Allen 2012; Hernandez, Cookson & Cortes 2021, Scarpa et al 2017), Globular clusters (Scarpa, Marconi & Gilmozzi 2003;Scarpa & Falomo 2010;Scarpa et al 2011;Hernandez & Lara-D I 2020), dwarf galaxies (Milgrom 1995;McGaugh & Milgrom 2013;Sanders 2021), gas dominated galaxies (McGaugh 2012; Sanders 2019), spiral galaxies (Sanders 1996;Gentile, Famaey & de Blok 2011;Milgrom & Sanders 2007), elliptical galaxies (Milgrom & Sanders 2003;Durazo et al 2018;Tian & Ko 2016), pair of galaxies (Milgrom 1983c), group of galaxies (Milgrom 2019;McGaugh et al 2021), gravitational lenses (Sanders 2014), and cluster of galaxies (Sanders 1999(Sanders , 2003. In all but one case MOND succeeds in describing the observations without the need of DM.…”
Section: An Alternative Dynamical Analysismentioning
confidence: 99%
“…To conclude this subsection we present the results of Tian and Ko (2016) who used the spherical Jeans equation to produce the MOND models for their sample of ETGs based on their PNe: they combined the PNe data (up to 6 − 8R e ) and stellar data from the SAURON database of seven elliptical galaxies, including three galaxies found in Romanowsky et al (2003) with updated data and four other ETGs which have not been analyzed before. Their sample included the following 7 galaxies: NGC 821, NGC 1344, NGC 3379, NGC 4374, NGC 4494, NGC 4697, and NGC 5846.…”
Section: Planetary Nebulae (Pne)mentioning
confidence: 99%